1992
DOI: 10.1128/jvi.66.12.7346-7354.1992
|View full text |Cite
|
Sign up to set email alerts
|

Strong trans activation of the human cytomegalovirus major immediate-early enhancer by p40tax of human T-cell leukemia virus type I via two repetitive tax-responsive sequence elements

Abstract: The immediate-early 1 and 2 gene locus of human cytomegalovirus (HCMV) that encodes trans-activator proteins with effects on both homologous and heterologous promoters is expressed under control of a complex enhancer/promoter regulatory region. This enhancer contains four types of repetitive sequence elements with 17, 18, 19, and 21 bp that bind cellular transcription factors. Although the HCMV enhancer acts as a powerfil stimulator of transcription in most cell types examined, human T cells do not support str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…An expression plasmid for IE2-p40 was created by inserting the SmaI-SalI fragment of the IE2-p86 cDNA into the EcoRV-SalI-cleaved vector pcDNA3. The luciferase reporter plasmids pHIVluc (HIV LTR upstream of luciferase) and 5GALluc (five GAL4 binding sites upstream of the adenovirus E1b promoter in front of luciferase) and the Tat expression vector pCT21 were obtained from C. Aepinus (Erlangen, Germany) (26,49). Plasmids pSCTGal-VP80 (encoding a GAL4 fusion with the activation domain of herpes simplex virus VP16) and GAL4-Oct1Q (encoding a GAL4 fusion with the activation domain of Oct1) FIG.…”
Section: Methodsmentioning
confidence: 99%
“…An expression plasmid for IE2-p40 was created by inserting the SmaI-SalI fragment of the IE2-p86 cDNA into the EcoRV-SalI-cleaved vector pcDNA3. The luciferase reporter plasmids pHIVluc (HIV LTR upstream of luciferase) and 5GALluc (five GAL4 binding sites upstream of the adenovirus E1b promoter in front of luciferase) and the Tat expression vector pCT21 were obtained from C. Aepinus (Erlangen, Germany) (26,49). Plasmids pSCTGal-VP80 (encoding a GAL4 fusion with the activation domain of herpes simplex virus VP16) and GAL4-Oct1Q (encoding a GAL4 fusion with the activation domain of Oct1) FIG.…”
Section: Methodsmentioning
confidence: 99%
“…However, Tax requires additional cellular DNA binding proteins to activate its target genes since Tax cannot bind to DNA by itself. Promoter analysis showed that the CREB binding elements located within the enhancer region of CMV MIE promoter are required for Tax transactivation of the CMV promoter 14. This observation raises the possible involvement of CREB/ATF family proteins in the Tax‐ dependent activation of the CMV MIE promoter.…”
Section: Resultsmentioning
confidence: 92%
“…Tax is also an oncogene and regulates several cellular genes that contribute to tumorigenesis, such as X‐box binding protein 1 (XBP‐1) 10–13. Besides cellular promoters, Tax has been shown to transactivate the CMV MIE promoter in a human T cell line, Jurkat 14. However, the impact of Tax on the CMV MIE promoter in other cell lines and the regulatory mechanism for Tax transactivation of the CMV promoter remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In 1990 Tada et al showed that the Tat protein of HIV-1 (human immunodeficiency virus 1) is able to trans-activate JC polyomavirus (JCV) late promoter which in turn led to the stimulation of JCV gene expression [ 31 ]. Two years later Moch et al showed that human T-cell lymphotropic virus 1 strongly trans-activated MIEP [ 24 ]. There were also cases of BKPyV transactivation reported.…”
Section: Discussionmentioning
confidence: 99%
“…Trans-activating viral proteins may affect the gene expression of host cells [ 22 ] as well as the genes of co-infecting virus [ 23 ]. In 1992 Moch et al showed a strong trans-activation of the human cytomegalovirus major immediate-early enhancer by human T-cell leukemia virus type 1 (HTLV-1) [ 24 ]. Two years later, Metvalf et al (1994) reported that the adenovirus E1A 13S gene product (an early protein 1A) up-regulates the cytomegalovirus major immediate early promoter [ 25 ].…”
Section: Introductionmentioning
confidence: 99%